COMPUTER MEDIATED COMMUNICATION (CMC) DALAM PEMBELAJARAN BAHASA INGGRIS - Risma Fahrul Amin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
The Industrial Revolution 4.0 has produced many breakthroughs especially the appearance of communication platforms that gave colour to English learning in Indonesia. Therefore computers are very useful in language class, although basically computers are only tools for mediating student’s communication in English learning. This paper describes Computer Mediated Communication (CMC) in English learning.